The Most Flowery Parnassus. Fables, Allegories and Emblems in Bolognese Nuptial Books of the First Half of the 17th Century - Emilia Montaner (TECA, 2014)
In the Seventeenth Century, Italian wedding cerimonies were followed up by the production of celebrative printings that the literary academies offered to the most illustrious families. In the context of those libretti per Nozze («publicaciones de ocasión» in Spanish), the inlustration played an important role. Focusing in particular on the famous painter and engraver Giovanni Luigi Valesio, this essay explores the relationship between iconography, texts and artistic models the nuptialia were based on in the city of Bologna during the Baroque period.